Empowered and embedded: ethics and agile processes. - Zuber, Niina; Gogoll, Jan; Kacianka, Severin; Pretschner, Alexander; Nida-Rümelin, Julian (Humanities & Social Sciences Communications, 2022)
This article focuses on the structural aspects of the development of ethical software, and argues that ethical considerations need to be embedded into the (agile) software development process. In fact, it is claimed that agile processes of software development lend themselves specifically well for this endeavor. First, it is contended that ethical evaluations need to go beyond the use of software products and include an evaluation of the software itself. This implies that software engineers influence peoples' lives through the features of their designed products. Embedded values should thus also be approached by software engineers themselves. Therefore, the emphasis is put on the possibility to implement ethical deliberations in already existing and well-established agile software development processes. The proposed approach relies on software engineers making their own judgments throughout the entire development process to ensure that technical features and ethical evaluation can be addressed adequately to transport and foster desirable values and norms. It is argued that agile software development processes may help the implementation of ethical deliberation for five reasons: (1) agile methods are widely spread, (2) their emphasis on flat hierarchies promotes independent thinking and autonomy, (3) their reliance on existing team structures serve as an incubator for deliberation, (4) agile development enhances object-focused techno-ethical realism, and, finally, (5) agile structures provide a salient endpoint to deliberation.